Applying Transfer Learning in Classification of Ischemia from Myocardial Polar Maps in PET Cardiac Perfusion Imaging - Hosseini, Seyed (My University, 2022)
Introduction: Ischemia is defined as the restriction of blood flow to a body organ, such as the heart, resulting in a cutback in oxygen supply. Myocardial ischemia is characterized by an imbalance between myocardial oxygen supply and demand, causing cardiac dysfunction, arrhythmia, myocardial infarction, and sudden death. Positron emission tomography myocardial perfusion imaging (PET-MPI) is an examination for accurately evaluating blood circulation to the heart muscle at stress and rest. Images obtained from this technique can be interpreted by experts or potentially classified by deep learning for the diagnosis of cardiac ischemia. Although deep learning has proved to be effective for medical image classification tasks, the challenge of small medical image datasets for model training remains to exist. Transfer learning is a state-of-the-art technique for resolving this challenge by utilizing pre-trained models for a new task. Pre-trained models are deep convolutional neural networks (CNNs) trained on a vast dataset, such as ImageNet, capable of transferring learned weights to a new classification problem. Objective: To study the effectiveness of image classification using transfer learning and benchmarking pre-trained CNN models for the classification of myocardial ischemia from myocardial polar maps in PET 15O-H2O cardiac perfusion imaging. Subject and methods: 138 JPEG polar maps from a 15O-H2O stress perfusion test from patients classified as ischemic or non-ischemic were used. Experiments for comparing a total of 20 pre-trained CNN models were performed. The results were compared against a custom CNN developed on the same dataset. Python programming language and its relevant libraries for deep learning were used. Results and discussion: Pre-trained models showed reliable performance compared to a custom-built CNN. VGG19, VGG16, DenseNet169, and Xception were superior among all pre-trained models. Ensemble learning improved overall performance, closest to the clinical interpretation level.
Keywords: Transfer learning, Deep learning, Myocardial Ischemia, PET Imaging, Convolutional neural networks